Analisis Faktor Sosial Ekonomi yang Mempengaruhi Keputusan Petani dalam Program Tunda Jual Gabah di Desa Sukarami Kecamatan Kota Agung , Kabupaten Lahat - Iskandar Malian (Jurnal Manajemen dan Bisnis, 2021)
Delay selling is an action to stabilize the price of agricultural commodities by indirectly selling the commodity at harvest (low price) but save first and sell at the time the price is felt stable. Farmers in marketing the results of farming have consideration in deciding to sell directly or postpone selling after harvest. Farmers' decisions are influenced by a number of factors. This study aims to describe the warehouse receipt system at the farm level and analyze the factors that affect the transaction costs at the farm level. The perception of rice farmers in sukarami Village about input indicators is very good category, whereas rice farmer perception about ouput indicator, yield, impact, and benefit are good category. The variables that influence the farmer's decision to apply the postponement system are the number of socialization attendance on the selling delay system and the distance of land to gapoktan. The more often the rice farmers in sukarami Village meghadiri socialization tug sales then farmers will have a chance to decide to do a system delay sale of 3,244 times. While the further distance of land to gapoktan then the farmers will have a chance to decide not to do system delay sale by 0.135 times.